Magmatism and Metallogeny in the Crustal Evolution of Rio Grande do Sul Shield, Brazil - HARTMANN, LÉO; NARDI, LAURO; FORMOSO, MILTON; REMUS, MARCUS; DE LIMA, EVANDRO; MEXIAS, ANDRÉ (Pesquisas em Geociências, 1999)
The State of Rio Grande do Sul has a complex Precambrian/Cambrian shield, which has been investigated for four decades. This complexity involves ages ranging from 2.55 Ga (possibly 3.3 Ga) to 550 Ma (and even 470 Ma). The three major juvenile accretionary episodes occurred at 2.55 Ga, 2.26-2.02 Ga and 900-700 Ma, while a continental-scale crustal reworking (collisional) orogeny occurred from 780 to 550 Ma. The three accretionary orogenies are known as the Jequié, Transamazonian and Brasiliano Cycles, respectively. The Brasiliano Cycle includes the collisional orogeny. Magmatism was tholeiitic low-K bimodal basic-acid in the Archean (Santa Maria Chico granulites), and evolved to tonalitic-trondhjemitic-granodioritic in the Paleoproterozoic (Encantadas Complex). During the Paleoproterozoic/Archean transition, komatiites and basalts were formed in greenstone belts (Passo Feio Sul Formation). The end of the Transamazonian Cycle was the beginning of a long period of tectonic quiescence, and the region remained in the interior of the Atlantica Supercontinent until the beginning of the Brasiliano Cycle at ca. 900 Ma (Passinho Diorite). This Neoproterozoic cycle displays two classical orogenic types, namely the São Gabriel accretionary orogeny in the western part of the State and Dom Feliciano collisional orogeny in its eastern part. Accretion generated juvenile tonalite-trondhjemite-granodiorite associations with related ophiolites (Cerro Mantiqueiras Ophiolite), while the collision formed the voluminous and mostly peraluminous and high-K calcalkaline granites of the Dom Feliciano orogeny. The waning stages of the orogeny were responsible for the outpouring of a very expressive silica-saturated volcanism and eventually finished with the Rodeio Velho basalts at 470 Ma. Comparable Paleoproterozoic/Neoproterozoic Precambrian terranes surround the shield in Uruguay, in Santa Catarina and in western Africa. Comparable Neoproterozoic juvenile and reworked terranes occur in NE Africa. Widespread indications of metals are a good sign of possible deposits, but the two major types of deposits are the orogenic epizonal Bossoroca gold deposit and the distal magmatichydrothermal Lavras/Camaquã copper-gold deposits.